Web Content Search and Adaptation for IDTV: One Step Forward in the Mediamorphosis Process toward Personal-TV. (24th May 2007) - Ferretti, Stefano; Roccetti, Marco; Palazzi, Claudio E.
Abstract : We are on the threshold of a mediamorphosis that will revolutionize the way we interact with our TV sets. The combination between interactive digital TV (IDTV) and the Web fosters the development of new interactive multimedia services enjoyable even through a TV screen and a remote control. Yet, several design constraints complicate the deployment of this new pattern of services. Prominent unresolved issues involve macro-problems such as collecting information on the Web based on users' preferences and appropriately presenting retrieved Web contents on the TV screen. To this aim, we propose a system able to dynamically convey contents from the Web to IDTV systems. Our system presents solutions both for personalized Web content search and automatic TV-format adaptation of retrieved documents. As we demonstrate through two case study applications, our system merges the best of IDTV and Web domains spinning the TV mediamorphosis toward the creation of the personal-TV concept.